Response of vegetation resilience to drought across river basins on a global scale - Muhammad Abrar Faiz; Faisal Baig; Shehakk Muneer; Zhaoqiang Zhou; Farah Naz (International Journal of Digital Earth, 2025)
Drought poses a critical threat to terrestrial vegetation. However, the differential vulnerability and resilience of various vegetation types under varying drought severities remain underexplored. Therefore, in this study, we aimed to investigate global vegetation resilience to meteorological drought from 2000 to 2023 and 2024 to 2099 under different climate change scenarios (i.e. shared socioeconomic pathways [SSPs]; SSP245 and SSP585). Using changes in the leaf area index (LAI) as a proxy, we quantified the influence of environmental factors and irrigation using a linear regression framework. The results reveal that major river basins had limited precipitation contributions, rendering them highly exposed to drought stress. However, irrigation was mitigated during and before drought, with contribution rates ranging between 20% and 47%. Short-term drought predictions under SSP245 via random forest regression indicate a strong impact of drought on evergreen and deciduous needleleaf forests. Wetlands and grasslands emerged as susceptible ecosystems, demonstrating increased vulnerability to water scarcity and short-term drought. This study provides important insights into the responses of different vegetation types to drought, highlighting the role of irrigation in enhancing drought resilience and underscoring the variability in elasticity across ecosystems.